Comparing the clinical utility and diagnostic performance of cerebrospinal fluid P‐tau181, P‐tau217 and P‐tau231 assays. (31st December 2021) - Leuzy, Antoine; Janelidze, Shorena; Mattsson‐Carlgren, Niklas; Palmqvist, Sebastian; Jacobs, Dirk; Cicognola, Claudia; Stomrud, Erik; Vanmechelen, Eugeen; Dage, Jeffrey L; Hansson, Oskar
Abstract: Background: Several studies indicate that increases in cerebrospinal fluid (CSF) phosphorylated tau (P‐tau) in Alzheimer's disease (AD) occur in response to very early amyloid‐β (Aβ) pathology and precede widespread tau aggregation. Thus far, however, there are no studies comparing different P‐tau isoforms—i.e., tau phosphorylated at threonine‐181 (P‐tau181), 217 (P‐tau217) and 213 (P‐tau231) levels—in relation to Aβ and Tau PET across the symptomatic stages of AD, nor data directly comparing their diagnostic performance for separating AD dementia from non‐AD neurodegenerative disorders and for identifying abnormal Aβ and Tau PET status. We herein aimed to address these questions using cross‐sectional data from the Swedish BioFINDER‐2 study. Method: We included cross‐sectional data for 629 participants (cognitively unimpaired, amyloid‐β (Aβ)‐positive mild cognitive impairment, Alzheimer's disease (AD) dementia and non‐AD disorders). In addition to comparing P‐tau181 and P‐tau217 measured using assays with the same capture antibodies from Eli Lilly (P‐tau181Lilly and P‐tau217Lilly ; Meso Scale Discovery platform) with P‐tau231 from ADx NeuroSciences (P‐tau231ADx ; sandwich ELISA), we also compared P‐tau181Lilly with P‐tau181 measurements from two commonly used assays (Innotest [P‐tau181Innotest ; sandwich ELISA] and Elecsys [P‐tau181Elecsys; fully automated electrochemiluminescence immunoassay]). Aβ and Tau PET were performed using [ 18 F]flutemetamol and [ 18 F]RO948.The discriminative performance of CSF P‐tau measures was assessed using the area under the receiver operating characteristic curve (AUC). Result: Though all P‐tau variants increased across the AD continuum, P‐tau217Lilly showed the greatest dynamic range (13‐fold‐increase vs 1.9‐5.4‐fold‐increase for other P‐tau variants for AD dementia vs non‐AD) (Figure 1). P‐tau217Lilly showed stronger correlations with Aβ‐ and tau‐PET ( P <0.0001) (Figure 2). P‐tau217Lilly exhibited higher accuracy than other P‐tau variants for separating AD dementia from non‐AD (AUC, 0.991vs 0.906‐0.982, P <0.0001) and for identifying Aβ‐PET positivity (AUC, 0.951 vs 0.816‐0.924, P <0.0001) and tau‐PET positivity (AUC, 0.957 vs 0.836‐0.938, P <0.0001) (Figure 3). Finally, P‐tau181Lilly generally performed better than the other P‐tau181 assays, (e.g., AD dementia vs non‐AD, AUC, 0.976 vs 0.923, P <0.0001). Conclusion: CSF P‐tau217Lilly seem to be more useful than other included P‐tau assays in the diagnostic work‐up of AD and for tracking disease progression. Varied results across P‐tau181 assays also highlights the importance of anti‐tau antibodies for biomarker performance.